Positioning dengan Teknologi Bluetooth Mengunakan Naïve Bayes Algoritma - Yusuf Eko Rohmadi; Taman Ginting; Didik Warasto (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2016)
Bluetooth has emerged as a viable choice of technology in indoor positioning systems due to the increase in the number of Bluetooth-enabled devices over the last decade. Bluetooth was initially developed as a cable replacement technology but properties such as low cost and high availability has led to the development of several indoor positioning systems relying on Bluetooth signals. The characteristics of the Bluetooth device’s RSSI (Received Signal Strength Indication) value were analyzed in preliminary experiments. According to the results of these experiments, the proposed method combines processing using RSSI value threshold and handling of instantaneous variation of RSSI value. Fingerprint data retrieval is done with each grid size 1m x 1m and 2m x 2m. RSSI measurements performed at room Politeknik Pratama Mulia Surakarta. Determination of the estimated location of the object is determined using Naïve Bayes algorithm From the research known influence on the measurements include a fingerprint grid sizes, algorithms and extensive amount of data from the fingerprint data measurement locations. The best results of testing of algorithms to generate distance 1m greatest accuracy. From the results with 1 meter got the result of 1.6 meters and 2 meters with 2:04 to scenario 2 results will be the first got the result 1.85m m2 and 2 m2 with the results of 2.06 The test results of unknown size on the grid one meter better than 2-meter grid.